2020
DOI: 10.1007/s13324-020-00364-5
|View full text |Cite
|
Sign up to set email alerts
|

Conjugations in $$L^2$$ and their invariants

Abstract: Conjugations in space L 2 of the unit circle commuting with multiplication by z or intertwining multiplications by z andz are characterized. We also study their behaviour with respect to the Hardy space, subspaces invariant for the unilateral shift and model spaces.Conjugations have recently been intensively studied and the roots of this subject comes from physics. An operator A ∈ B(H) is called C-symmetric if C AC = A * (or equivalently AC = C A * ). A strong motivation to study conjugations comes from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 14 publications
6
38
0
Order By: Relevance
“…There is a natural conjugation (an antiunitary involution) connected with a model space (see for instance [5,12]). For an inner function θ define…”
Section: Conjugationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a natural conjugation (an antiunitary involution) connected with a model space (see for instance [5,12]). For an inner function θ define…”
Section: Conjugationmentioning
confidence: 99%
“…Model spaces, which provide the natural setting for truncated Toeplitz operators, have generated enormous interest and they are relevant in connection with a variety of topics such as the Schrödinger operator, classical extremal problems in control theory, Hankel operators and Toeplitz matrices (see for instance [13] and [11]). Natural conjugations, which model spaces and the whole L 2 possess (see [5]), make model spaces even more natural in the context of pysics [12]. Their orthogonal complements in L 2 also appear in numerous applications.…”
Section: Introductionmentioning
confidence: 99%
“…In [2,Theorem 2.4] all conjugations in L 2 commuting with M z were characterized. In particular it was shown that such a conjugation has to be of the form M ψ J for some unimodular function ψ ∈ L ∞ which is symmetric, i.e., ψ(z) = ψ(z) a.e.…”
Section: Conjugations In L 2 ⊕ Lmentioning
confidence: 99%
“…In [2,3] all conjugations in the classical L 2 space on the unit circle commuting with M z or intertwining the operators M z and Mz (in other words, all conjugations C according to which the operator M z is C-symmetric, see the definition below) were fully characterized. The behaviour of such conjugations was also studied in connection with an analytic part of the space L 2 and model spaces, in particular there were characterized all conjugations leaving the whole Hardy space and model spaces invariant.…”
Section: Introductionmentioning
confidence: 99%
“…E.g. all conjugations in L 2 space of the unit circle commuting with M z or intertwining operators M z and M̄z (in other words all conjugations C according to which the operator M z is C-symmetric, see the definition below) are completely characterized in [3,5]. In [4] similar description is given for L 2 spaces of vector valued functions.…”
Section: Introductionmentioning
confidence: 99%